2020
DOI: 10.1016/j.jcbs.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Psychological flexibility, coping, mental health, and wellbeing in the UK during the pandemic

Abstract: The COVID-19 pandemic has profoundly altered the daily lives of many people across the globe, both through the direct interpersonal cost of the disease, and the governmental restrictions imposed to mitigate its spread and impact. The UK has been particularly affected and has one of the highest mortality rates in Europe. In this paper, we examine the impact of COVID-19 on psychological health and well-being in the UK during a period of ‘lockdown’ (15th–21st May 2020) and the specific role of Psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
298
4
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(358 citation statements)
references
References 58 publications
(74 reference statements)
44
298
4
12
Order By: Relevance
“…Thus, after controlling for levels of the variables in the previous waves of assessment, relative spikes in inflexibility within wave 2 or 3 predicted corresponding spikes in symptoms within that same wave. Although these results do not demonstrate a cause-effect relationship between changes in psychological inflexibility and changes in mental health symptoms because the associations are crossectional (see Cole & Maxwell, 2003 ), our results are nonetheless congruent with the theory that psychological inflexibility likely interferes with effective coping under distress and leads to poor mental health (e.g., Dawson & Golijani-Moghaddam, 2020 ; Karekla & Panayiotou, 2011 ). The results are also akin to the finding that lack of psychological flexibility may diminish resilience to accumulated major life events and their perceived negative impact ( Fonseca et al, 2019 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, after controlling for levels of the variables in the previous waves of assessment, relative spikes in inflexibility within wave 2 or 3 predicted corresponding spikes in symptoms within that same wave. Although these results do not demonstrate a cause-effect relationship between changes in psychological inflexibility and changes in mental health symptoms because the associations are crossectional (see Cole & Maxwell, 2003 ), our results are nonetheless congruent with the theory that psychological inflexibility likely interferes with effective coping under distress and leads to poor mental health (e.g., Dawson & Golijani-Moghaddam, 2020 ; Karekla & Panayiotou, 2011 ). The results are also akin to the finding that lack of psychological flexibility may diminish resilience to accumulated major life events and their perceived negative impact ( Fonseca et al, 2019 ).…”
Section: Discussionsupporting
confidence: 52%
“…Such hypothesis is compatible with both crossectionally (e.g., Gloster et al, 2017 ) and prospectively (e.g., Shallcross et al, 2010 ) found associations between inflexibility and mental health outcomes. The COVID-19 pandemic presents a naturally occurring opportunity to test this hypothesis, given that the challenges imposed by the lockdown and related stress appear to impact inflexibility, as well as mental health outcomes (e.g., Arslan et al, 2020 ; Dawson et al, 2020 ; Pakenham et al, 2020 ). To our knowledge, no study has explored how psychological inflexibility changes along a sustained period of befallen impactful daily life challenges comparable to those derived from the COVID-19 pandemic, and how this may relate to changes in mental health symptoms over time.…”
Section: Introductionmentioning
confidence: 99%
“…Validated versions of the tests in the various languages spoken in the seven countries were employed. Moreover, considering previous researches performed on a one-country level, IES-R and DASS-21 were used during COVID-19 research in China ( Hao et al., 2020 ), India ( Chew et al., 2020 ), Vietnam ( Le et al., 2020 ), Singapore ( Tan et al., 2020 ), and Philippines ( Tee et al., 2020 ); MASS was adopted in Italy ( Conversano et al., 2020 ; Baiano et al., 2020 ) and Brazil (Kozasa et al., 2020); PSS10 was used in Brazil (Kozasa et al., 2020), China ( Duan et al., 2020 ; Yan et al., 2020 ) and Colombia ( Pedrozo-Pupo et al., 2020 ); PHQ9 was employed in Greece ( Skapinakis et al., 2020 ), Italy ( Rapisarda et al., 2020 ), Spain ( Garre-Olmo et al., 2021 ) and China ( Yao, 2020 ); Brief-COPE was used in Australia ( Gurvich et al., 2020 ), Greece ( Skapinakis et al., 2020 ), United Kingdom ( Dawson and Golijani-Moghaddam, 2020 ) and USA ( Umucu and Lee, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The online survey was distributed using snowball sampling, which is in line with similar previous studies (19)(20)(21). The initial group of respondents was contacted via project members' professional (healthcare professionals) and personal contacts (general population), and the link to the survey was disseminated further via the Facebook social network.…”
Section: Data Collectionmentioning
confidence: 99%